Evidence-based medicine and Management of Hepatocellular Carcinoma in Thalassemia - Mancuso, Andrea (BMC Gastroenterol, 2020)
BACKGROUND: Hepatocellular carcinoma as a complication is linked to improved outcomes of thalassemia. MAIN BODY: Published data suggest an incidence of HCC in thalassemia of about 2%. However, since thalassemia is endemic in many under-developed countries where patients have not probably been screened for HCC yet, the burden of the disease could be higher. Prevention of HCV infection through blood transfusion, HCV treatment and adequate iron chelation are all tools to prevent HCC in thalassemia. In presence of risk factors, HCC screening seems appropriate for thalassemia. Management of HCC should not be different from that indicated for non thalassemics. However, liver transplantation can be challenging and should be reserved to highly selected cases, due to coexistence of relevant comorbidities. Decisions in the management of HCC in thalassemia should follow a multidisciplinary effort. Moreover, due to the paucity of published data about the issue, future multicenter international studies will be helpful. SHORT CONCLUSION: In BMC Gastroenterology results of a commendable effort to guidelines for the management of HCC in thalassemia are reported by an Italian panel of experts. However, due to the paucity of published data about the topic, some conclusions rely on grey areas and are reason of debate.